2012
DOI: 10.1111/j.1747-1567.2012.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Techniques for Lateral Stability Testing of Beams

Abstract: This paper presents experimental setups used in lateral stability tests of beams. The load frame of the setup effectively eliminates the lateral‐translational and torsional restraints at the load application point, while maintaining the vertical orientation of the applied load, despite the lateral deformations and twisting rotations in the specimen. Two different support frames used in the experiments are also presented. The first support frame provides simple support conditions in‐ and out‐of‐plane and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…König and Pauli (1990) utilized steel and water weights as the distributed load mechanism to perform the lateral and torsional buckling experiment in reinforced and prestressed concrete beams. The distributed load mechanism has limitations on space, logistics, and safety, which has rarely been applied in the test (Kalkan and Hurff 2012). Therefore, most of the lateral and torsional buckling experiments have attempted to use a point load mechanism to retain the initial vertical and concentrical position of the applied load without its resistance to the lateral and torsional restraints of the test beam at the loading point.…”
Section: Vertical Loading Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…König and Pauli (1990) utilized steel and water weights as the distributed load mechanism to perform the lateral and torsional buckling experiment in reinforced and prestressed concrete beams. The distributed load mechanism has limitations on space, logistics, and safety, which has rarely been applied in the test (Kalkan and Hurff 2012). Therefore, most of the lateral and torsional buckling experiments have attempted to use a point load mechanism to retain the initial vertical and concentrical position of the applied load without its resistance to the lateral and torsional restraints of the test beam at the loading point.…”
Section: Vertical Loading Systemmentioning
confidence: 99%
“…Therefore, many studies (i.e., Hansell and Winter 1959;Sant and Bletzacker 1961;Massey 1967;Siev 1960;Revathi and Menon 2007a, b) used roller bearing and ball-and-socket joint mechanisms to minimize the resistance to the lateral and rotational deformations of the test beam at the loading point during the test. Kalkan and Hurff (2012) indicated that the roller bearing mechanism could induce load eccentricity due to some difference between the centroid of the applied load and the beam when the specimen undergoes lateral deformation. Therefore, another load mechanism using a gravity load simulator, which was originally designed by Yarimci et al (1967) to apply a vertical load to a full-scale frame experiment, was used in the lateral and torsional buckling experiments on full-scale steel I-beams (Yura and Phillips 1992;Helwig et al 2005), composite I-beams (Stoddard 1997), and reinforced concrete beams (Kalkan 2014;Hurff and Kahn 2012).…”
Section: Vertical Loading Systemmentioning
confidence: 99%